Pain reduction by hypericum scabrum extract in rats with long-term high-fat diet-induced obesity - Arezoo Rezvani-Kamran; Somayeh Komaki; Ghazaleh Omidi; Ali Fathi Jouzdani; Parisa Hasanein; Farshid Etaee; Alireza Komaki (Discover Applied Sciences)
Abstract Background Obesity, often linked to chronic pain, is exacerbated by high-fat diets (HFD). Antioxidants with anti-inflammatory properties may alleviate pain, and Hypericum scabrum, a plant rich in bioactive compound, shows potential in this regard. This study investigated the analgesic effects of H. scabrum extract in HFD-fed male rats using hot-plate (HP) and tail-flick (TF) tests. Methods Fifty-four male Wistar rats (220 ± 10 g) were randomly assigned to six groups: (a) control (standard diet), (b) extract 100 (standard diet + extract (100 mg/kg) once per day), (c) extract 300 (standard diet + extract (300 mg/kg) once per day), (d) HFD, (e) HFD + extract 100 (extract at 100 mg/kg once per day), and (f) HFD + extract 300 (extract at 300 mg/kg once per day). Animals were fed for 3 months and then, the antinociceptive effects were assessed using the HP and TF tests. A P-value of less than 0.05 was considered significant. Results In the tail-flick test, Ext 300 mg/kg and HFD + Ext 300 mg/kg increased latency versus control (p < 0.01; p < 0.05), while HFD decreased latency (p < 0.01). A dose-dependent effect was observed (Ext300 versus Ext100: p < 0.01), with HFD + Ext300 surpassing HFD + Ext100 (p < 0.05) and HFD (p < 0.001). In the hot plate test, Ext300 prolonged reaction time versus Ext100 (p < 0.01) and HFD (p < 0.01); HFD + Ext300 outperformed HFD + Ext100 (p < 0.05) and HFD (p < 0.001). HFD increased weight versus control (p < 0.0001), mitigated by Ext100 (p < 0.05) and Ext300 (p < 0.001). Conclusions The extract of H. scabrum due to its potent antioxidants has nociceptive effects on the HFD and control groups and increased pain tolerance; the pain sensitivity is a result of chronic consumption of HFD in animals.